Targeted synthesis of a positional isomer of aromatic N-methyl N-confused corrole and its organocopper(III) complex - Panua, Anirban; Velmurugan, Gunasekaran; Comba, Peter; Rath, Harapriya (Chemical communications, 2025)
We report the synthesis, spectroscopic analyses and solid-state structural evidence of an unprecedented positional isomer of aromatic [18] N-confused corrole exhibiting vis-NIR absorption. Copper metalation led to an organo-copper(III) complex with preserved aromaticity.
Erstveröffentlichung: 6. Oktober 2025
Gesehen am 02.02.2026